PERBEDAAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIK ANTARA SISWA YANG DIBERI PEMBELAJARAN KOOPERATIF TIPE THINK-TALK-WRITE DENGAN PEMBELAJARAN LANGSUNG - Putri Maisyarah Ammy; Ismail Hanif Batubara (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The purposes of this study were to investigate: (1) Differences in mathematics conceptual understanding ability among students who are given a learning cooperative type Think-Talk-Write model with students who were given direct learning model. (2) To describe the active activity of student during learning cooperative type Think-Talk-Write. (3) To describe the accomplishing of student answers in learning cooperative type Think-Talk-Write and direct learning. This was a semi-experimental study. The population was first grade students of SMP Muhammadiyah 1 Medan. Then randomly selected two classes of six grade. The experimental class ware given learning cooperative type Think-Talk-Write model and control classes were subjected to direct teaching model. The instruments consisted of: (1) Mathematics conceptual understanding test, and (2) Observation sheet. Data analysis was performed by analysis of covariance (ANACOVA). The results showed that (1) There are differences in mathematics conceptual understanding among students who are given a model of learning cooperative type Think-Talk-Write with students who were direct instruction model. This is evident from the results ANACOVA to Fhitung = 37,457 is greater Ftabel 4,01. Constants of regression equations to model problem-based learning that is 27,027 greater than the direct learning model is 26,454. (2) The activity levels of active student has met the ideal percentage of time set. (3) the completing of students answers that are taught by learning cooperative type Think-Talk-Write model are better than students whorm are taught by using direct instruction model.Keywords: Think-Talk-Write, Mathematics Conceptual Understanding